Molecular Basis and Clinical Overview of McLeod Syndrome Compared With Other Neuroacanthocytosis Syndromes: A Review - Roulis, Eileen; Hyland, Catherine; Flower, Robert; Gassner, Christoph; Jung, Hans H; Frey, Beat M (JAMA neurology, 2018)
McLeod syndrome, encoded by the gene XK, is a rare and progressive disease that shares important similarities with Huntington disease but has widely varied neurologic, neuromuscular, and cardiologic manifestations. Patients with McLeod syndrome have a distinct hematologic presentation with specific transfusion requirements. Because of its X-linked location, loss of the XK gene or pathogenic variants in this gene are principally associated with the McLeod blood group phenotype in male patients. The clinical manifestation of McLeod syndrome results from allelic variants of the XK gene or as part of a contiguous gene deletion syndrome involving XK and adjacent genes, including those for chronic granulomatous disease, Duchenne muscular dystrophy, and retinitis pigmentosa. McLeod syndrome typically manifests as neurologic and cardiologic symptoms that evolve in individuals beginning at approximately 40 years of age. Diagnosis of McLeod syndrome encompasses a number of specialties, including neurology and transfusion medicine. However, information regarding the molecular basis of the syndrome is incomplete, and clinical information is difficult to find. The International Society of Blood Transfusion has recently compiled and curated a listing of XK alleles associated with the McLeod phenotype. Of note, McLeod syndrome caused by structural variants as well as those cases diagnosed as part of a contiguous gene deletion syndrome were previously classified under a singular allele designation. This review discusses the clinical manifestations and molecular basis of McLeod syndrome and provides a comprehensive listing of alleles with involvement in the syndrome published to date. This review highlights the clinical diversity of McLeod syndrome and discusses the development of molecular tools to elucidate genetic causes of disease. A more precise and systematic genetic classification is the first step toward correlating and understanding the diverse phenotypic manifestations of McLeod syndrome and may guide clinical treatment of patients and support for affected and carrier family members. This review provides a knowledge base for neurologists, hematologists, and clinical geneticists on this rare and debilitating disease.